Mechanistic investigations on emission characteristics from g-C3N4, g-C3N4@Pt and g-C3N4@Ag nanostructures using X-ray absorption - Sharma, Aditya; Varshney, Mayora; Chae, Keun Hwa; Won, Sung Ok (ELSEVIER SCIENCE BV, 2018)
An improved method for the preparation of g-C3N4 is described. Currently, heating ( > 400 C degrees) of urea is the common method used for preparing the g-C3N4. We have found that sonication of melamine in HNO3 solution, followed by washing with anhydrous ethanol, not only reduce the crystallite size of g-C3N4 but also facilitate intriguing electronic structure and photoluminescence (PL) properties. Moreover, loading of metal (Pt and Ag) nanoparticles, by applying the borohydride reduction method, has resulted in multicolor-emission from g-C3N4. With the help of PL spectra and local electronic structure study, at C K-edge, N K-edge, Pt L-edge and Ag K-edge by X-ray absorption spectroscopy (XAS), a precise mechanism of tunable luminescence is established. The PL mechanism ascribes the amendments in the transitions, via defect and/or metal states assimilation, between the pi* states of Iris-triazine ring of g-C3N4 and lone pair states of nitride. It is evidenced that interaction between the C/N 2p and metal 4d/5d orbitals of Ag/Pt has manifested a net detraction in the delta*-> LP transitions and enhancement in the pi*-> LP and pi*->pi at transitions, leading to broad PL spectra from g-C3N4 organic semiconductor compound.
Keywords: GRAPHITIC CARBON NITRIDE; PHOTOCATALYTIC ACTIVITY; GRAPHENE-OXIDE; SPECTROSCOPY; NANOCATALYST; XANES; EXAFS